A Case of Very Late Onset Schizophrenia-Like Psychosis Presenting in a Patient Forty Years Post Acoustic Neuroma Resection - Sita Shah; Emad Sidhom; Cristina Levinte; Eladia Ruiz-Mendoza; Julius Essem (BJPsych Open, 2025)
Aims: Very late onset schizophrenia-like psychosis (VLOSLP) can be defined as individuals presenting with symptoms of psychosis after the age of 60 that cannot be attributed to an “affective disorder or focal or progressive structural brain abnormality”. Despite being described by an international group consensus in 1998, this diagnosis is not included in ICD–11 or DSM–5 manuals.